Voices From The Frontline: A Collective Viewpoint Of Medical Practitioners In Saudi Arabia (The Review of Diabetic Studies, 2024)
Healthcare in the Kingdom of Saudi Arabia is undergoing significant change, defined by Saudi Vision 2030 and the Health Sector Transformation Program (HSTP). From the frontline, this transformation isn't an abstract policy agenda—it is a daily operational reality that influences how we triage, diagnose, treat, rehabilitate, educate, and protect communities. Across all disciplines, we share the responsibility of translating national strategy into safe, equitable, patient-focused care.